Inhibition of NA+/H+ Exchanger 1 Attenuates Renal Dysfunction Induced by Advanced Glycation End Products in Rats. (30th November 2015) - Li, Peng; Chen, Geng-Rong; Wang, Fu; Xu, Ping; Liu, Li-Ying; Yin, Ya-Ling; Wang, Shuang-Xi
Abstract : It has been recognized that sodium hydrogen exchanger 1 (NHE1) is involved in the development of diabetic nephropathy. The role of NHE1 in kidney dysfunction induced by advanced glycation end products (AGEs) remains unknown. Renal damage was induced by AGEs via tail vein injections in rats. Function and morphology of kidney were determined. Compared to vehicle- or BSA-treated rats, AGEs caused abnormalities of kidney structures and functions in rats, accompanied with higher MDA level and lower GSH content. Gene expressions of NHE1 gene and TGF- β 1 in the renal cortex and urine were also increased in AGEs-injected rats. Importantly, all these detrimental effects induced by AGEs were reversed by inhibition of NHE1 or suppression of oxidative stress. These pieces of data demonstrated that AGEs may activate NHE1 to induce renal damage, which is related to TGF- β 1.